E-Learning Challenges in Iran: A Research Synthesis - Abbasi Kasani, Hamed; Shams Mourkani, Gholamreza; Seraji, Farhad; Rezaeizadeh, Morteza; Abedi, Hojjat (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2020)
This study investigates and fully identifies the challenges of the Iranian e-learning system. The approach was qualitative and the method was research synthesis. The statistical population consisted of studies from 2006 to 2019 in the field of challenges of the e-learning system of Iran collected with specific keywords from the country’s databases. A total of 48 studies were identified as relevant. They were screened in stages and evaluated based on their title, abstract, and content. The final 19 articles selected underwent content analysis, revealing that Iran’s e-learning system faces problems in eight dimensions: legal, human, educational, technological, sociocultural, support, economic, and managerial-organizational. The results of the analysis could serve as a model for countries with similar technology infrastructure and cultural features wishing to improve their e-learning systems.